The relationship between depression levels and substance use and family attitudes in university students - San, Anıl; Erensoy, Habib; Aytaç, Hasan Mervan; Berkol, Tonguç Demir (Journal of Dependence, 2020)
Objective: The aim of this study was to investigate the relationship between depression symptom severity, substance abuse and family attitudes in university students. Method: The target population of the study is the students who are studying at the same university and the sample is composed of 100 students at the same university. In our research, "Sociodemographic Form", "Hamilton Depression Rating Scale" and "Parent Attitude Scale" were applied to the university students. The scales were applied to the participants in one on one interviews. Results: According to the class variable, the democratic attitude levels of the 1st grade students are significantly higher than the students of other grades. A medium-level positive meaningful correlation between depression level and substance addiction has been identified. While there is no relationship between depression level and parent attitudes, there is also no relationship between substance addiction and parent attitudes. Conclusion: No relationship was found between depression symptom severity and parental attitudes and between substance use and parental attitudes, important risk factors affecting substance use were easy access of the substance, attitudes towards illegal drugs, misuse of drugs and familial problems.